Correlation of the Role of Drug Swallowing Supervisor (PMO) and Drug Side Effects with Medication Compliance in Elderly Pulmonary TB Patients - Benyamin Tampang; Wiyadi; Mustaming (Asian Journal of Healthcare Analytics, 2023)
The 2019 World Health Organization notes that tuberculosis is a disease that is still a global concern. Indonesia has the 3rd highest number of cases after India and China. The target rate for medication adherence in Berau Regency, which is included in the elderly age group, has not been achieved due to the lack of PMO support and the side effects of the drugs experienced. The type of research used is analytical research which is carried out only through observation, without any intervention on the research subject. Statistical test results showed that there was no significant relationship between drug side effects and medication adherence with a pvalue of 0.273 > 0.05.